Evolution of four-decade atmospheric mercury release from a coal-fired power plant in North China. (15th September 2019) - Li, Zhonggen; Chen, Xufeng; Liu, Wenli; Li, Taishan; Chen, Ji; Lin, Che-Jen; Sun, Guangyi; Feng, Xinbin
Abstract: Coal-fired power plants (CFPPs) are an important anthropogenic emission source of atmospheric mercury (Hg). Understanding the co-benefits of conventional air pollution control devices (APCDs) on Hg reduction is crucial for reducing Hg emission from this source. In this study, atmospheric Hg emission from a pulverized coal (PC) utility boiler in North China was investigated along the emission control stage of selective catalytic reduction (SCR), electrostatic precipitator (ESP) and fabric filter (FF) and lime stone-gypsum wet flue gas desulfurization (WFGD). Historical atmospheric Hg emission from this CFPP with total 1550 MW capacity since its operation in 1976 was estimated based on the implementation of different configurations of APCDs. The results showed that a combination of SCR + ESP-FF + WFGD leads to a co-beneficial Hg control of 96%, with the in-stack Hg concentration (0.87 μg m −3 ) much lower than the Chinese national standard for CFPPs (30 μg m −3 ), and the stack Hg speciation (Hg 0 :Hg 2+ :Hg p ) was in 86%:13%:1%. Mass balance analysis indicates that Hg from the input of feed coal and limestone was mainly ended up in fly ash (89%), followed by gypsum (5%), stack gas (5%) and bottom ash (1%), respectively. During the past 42 years of operation (1976–2017), the total air Hg emission from this CFPP summed to 17.62 tonnes, in which Hg 0 make up 14.02 tonnes (79.5%), Hg 2+ make up 3.15 tonnes (17.9%) and Hg p 0.45 tonne (2.6%). Although the speciation of emitted Hg into the atmosphere changed with respect to the configuration of APCDs, Hg 0 was the most dominated emission species (64–98%) for all time. Nearly 90% of total Hg emissions occurred in the first three decades when venturi scrubber (VS) and ESP were the primary APCDs. The installation of WFGD and SCR substantially decreased the Hg emission factors by 17 times compared to the peak values during 1998–2004. This study demonstrates the combination of SCR + ESP-FF + WFGD as a best available technology (BAT) for Hg control in CFPPs in China. Graphical abstract: Image 1 Highlights: Installation of WFGD, ESP-FF and SCR dramatically reduced the Hg emission factors. >95% Hg removal from CFPP flue gases was accomplished with SCR + ESP-FF + WFGD. Captured Hg remained mainly in ESP-FF fly ash and followed by WFGD gypsum. 17.6 tonnes of Hg was cumulatively released into ambient air from 1976 to 2017. Hg 0 :Hg 2+ :Hg p in a ratio of 79.5%:17.9%:2.6% for emitted Hg into atmosphere in the past four decades.